Regionalization strategies of SME sector : an empirical study of Singapore managers / Samir Ranjan Chatterjee and Lim Cheng Hwa - Chatterjee, Samir Ranjan; Lim, Cheng Hwa (Faculty of Business and Management ; UiTM Press, 2000)
The closing years of the twentieth century have been marked by an unprecedented intensification of global integration for national economies. In recent years, the government of Singapore had responded to this global imperative by vigorously encouraging the regionalization of SME sector. The professionalisation of the management in the SME sector was emphasised as the critical factor in achieving this strategic shift. The study reported in this paper, presents empirical evidency of managerial perceptions and the explorations of this challenge. Considerable range of factors were identified as being the facilitators and roadblocks .to the regionalization of SMEs as they responded to new challenges. The driving force of new market opportunity, alliances with other firms, quality of product and design, innovative shift to new industries and similar ideas were considered. The findings outlined in this paper tends to indicate that side by side with domestic growth; regional strategy was becoming more significant in the recent years.